KI 2016 : advances in artificial intelligence : 39th Annual German Conference on AI, Klagenfurt, Austria, September 26-30, 2016, Proceedings /: advances in artificial intelligence : 39th Annual German Conference on AI, Klagenfurt, Austria, September 26-30, 2016, Proceedings. (2016) - Unknown
No abstract available